Complete neutralization of the lethality of Hemiscorpius lepturus crude venom by a novel anti-recombinant phospholipase D1 IgGs. (August 2020) - Torabi, Elham; Behdani, Mahdi; Khalaj, Vahid; Pooshang Bagheri, Kamran; Shahbazzadeh, Delavar
Abstract: Treatment of scorpion envenomation is a challenging issue since serotherapy is implemented by administration of polyvalent equine antisera. In our previous study we discovered that recombinant phospholipase D1 (Hl-RecPLD1) is responsible for the lethality of Hemiscorpius lepturus (H. lepturus) venom in mice. Accordingly, this study was aimed to investigate the protectivity of purified anti-Hl-RecPLD1 IgG against the lethality or major complications of H. lepturus venom. The neutralization efficiency of purified anti-Hl-RecPLD1 IgGs against sphingomyelinase activities of the crude venom and Hl-RecPLD1 was also assessed. Anti-Hl-RecPLD1 IgGs at optimum amount of 3.7 mg completely neutralized one Lethal Dose 100 (LD100 ) of crude venom in mice. The anti-Hl-RecPLD1 IgGs remarkably reduced the necrosis area from 6.5 to 1 cm 2 in rabbit derma, induced by the crude venom. The anti-Hl-RecPLD1 IgGs remarkably reduced the sphingomyelinase and hemolytic activities of crude venom as well. In conclusion, a novel rabbit monovalent IgG against Hl-RecPLD1 was able to completely protect the mice against the lethality of H. lepturus crude venom and reduced its toxicity as well. Such monovalent anti-Hl-RecPLD1 IgGs may have potential applications in serotherapy of H. lepturus envenomation. Highlights: Anti-Hemiscorpius lepturus recombinant phospholipase D1 protected the mice against lethality. Anti-recombinant phospholipase D1 prevented the hemolytic and dermonecrotic activity of venom. Anti-recombinant phospholipase D1 is a monospecific neutralizing antibody. The neutralizing efficiency of the antibody was similar to the commercial antisera.